(untitled) (Revista Interdisciplinar de Pesquisa em Engenharia, 2017)
Abstract. In this paper the Arduino microcontroller together with the gyroscopic sensor for measuring vibrations in mechanical systems are used. The objective is to present the Arduino platform as an alternative for low cost signal acquisition, easy use and good precision for educational purpose. In this application the system presents a nonlinear behavior for certain initial conditions. The characterization of the system’s nonlinearities are done by the comparison between the signal measured and a numerical solution of the classic equation of motion of the pendulum. It is also presented a scenario where the pendulum is excited by an magnetic interaction. The results showed in conformity with the literature. Keywords: Arduino microcontroller, sensor, vibrations, nonlinear, education